1993
DOI: 10.1002/jbm.820270513
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the extractive and hydrolytic behavior of microthane poly(ester‐urethane) foam by high pressure liquid chromatography

Abstract: Microthane foam, a poly(ester-urethane) (PU) used in the manufacture of Meme/Replicon breast implants, was analyzed by an HPLC method to determine whether 2,4- and 2,6-toluenediamine (TDA) were formed under a variety of physiological and nonphysiological extraction and hydrolytic conditions. At our detection limit of 20 ppb, no 2,4- or 2,6-TDA was observed in either methyl tert-butyl ether (MTBE), or aqueous buffer extracts of PU foam. The predominant extractable components identified by HPLC UV-analysis, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…One of the degradation products of TDI is 2,4-toluenediamine (2,4-TDA). Data in experimental animals showed that the PU foam cover degraded within [6][7][8][9][10][11][12] months of implantation (2). This result was consistent with the clinical observations in patients with Meme breast implants (3,4).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…One of the degradation products of TDI is 2,4-toluenediamine (2,4-TDA). Data in experimental animals showed that the PU foam cover degraded within [6][7][8][9][10][11][12] months of implantation (2). This result was consistent with the clinical observations in patients with Meme breast implants (3,4).…”
supporting
confidence: 77%
“…Our own in vitro studies indicated that 2,4-TDA was slowly released over time by hydrolytic degradation when PU foam samples were incubated under mild physiological conditions (5,6). The amount and rate of 2,4-TDA production observed in vitro varied with the conditions of PU foam exposure (7)(8)(9). The carcinogenicity of 2,4-TDA was studied extensively in mice, rats, and other species (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…This enhancement is supported by evidence found in the l i t e r a t~r e .~,~,~~ The rate of TDA formation from PU foam degradation was 250 ng/g/day . Samples of PU foam were exposed for 3,5,7,16,20,21,28, and 36 days in phosphate buffer at 37 "C. At an appropriate time point, the buffer was collected, filtered, and carried through the methylene chloride extraction/concentration procedure. Quantification of TDA was done using reverse phase HPLC with UV PDA detector.…”
Section: Resultsmentioning
confidence: 99%
“…The as-received sheets of PU foam (3 g) were carefully weighted, cut in strips, and placed in a liter screw-capped (teflon-lined) Wheaton bottle filled with 300 mL phosphate buffer pH 7.4 or methylene chloride. The extraction bottles were placed on magnetic stirrers to provide the gentle stirring in an environmental chamber at 37 "C, or in an oven at 50 "C. The PU foams (n = 3) were extracted in PO4 buffered solutions pH 7.4 for 3,5,7,16,20,21,28, and 36 days at 37 "C and for 3,7,16,22,27,30, and 38 days at 50 "C. For methylene chloride extraction, PU foam samples were extracted in CH2CIz for a total of 60 days at 37 "C to determine the total residual TDA remaining from the manufacturing process. The solvents were exchanged for fresh solvent on day 5 and extraction was continued until day 60 at 37 "C. One sample was extracted at room temperature for 27 days.…”
Section: Experimental Sample Preparation For Tda Analysismentioning
confidence: 99%
“…Medical uses of polyurethanes have typically been polyester and polyether based formulations. Polyether urethanes degrade by oxidation of the ether linkage by cellular substances, typically superoxide and hydrogen ion releases from the granules of leukocytes and macrophages (Zhao, McNally et al 1993), while the degradation mechanism of polyester urethanes is hydrolysis (Amin, Willie et al 1993). …”
Section: Synthetic Tri-leaflet Heart Valvesmentioning
confidence: 99%